A review for the pharmacological effects of paeoniflorin in the nervous system - Hong, Hongxiang; Lu, Xu; Wu, Chunshuai; Chen, Jiajia; Chen, Chu; Zhang, Jinlong; Huang, Chao; Cui, Zhiming (Frontiers in Pharmacology, 2022)
Paeoniflorin, a terpenoid glycoside compound extracted from Paeonia lactiflora Pall, shows preventive and therapeutic effects in various types of nervous system disorders. However, to date, no comprehensive knowledge on the pharmacological effects of paeoniflorin on the nervous system is available online. Clarification of this issue may be useful for the development of paeoniflorin as a new drug for the treatment of nervous system disorders. To this end, the authors summarize the pharmacological aspects of paeoniflorin and its possible mechanisms, such as restoration of mitochondrial function; inhibition of neuroinflammation, oxidative stress, and cellular apoptosis; activation of adenosine A1 receptor, cAMP response element-binding protein (CREB) and extracellular signal-regulated kinase 1/2 (ERK1/2); or enhancement of brain-derived neurotrophic factor (BDNF) and serotonin function, in the prevention of disorders such as cerebral ischemia, subarachnoid hemorrhage, vascular dementia, Alzheimer’s disease, Parkinson’s disease, depression, post-traumatic syndrome disorder, and epilepsy, by reviewing the previously published literature.